2018
DOI: 10.1016/j.jappgeo.2018.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Agglomerative hierarchical clustering of airborne electromagnetic data for multi-scale geological studies

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
0
13
0
3
Order By: Relevance
“…Many studies reported methods, approaches and algorithm to better process and model data aimed at highlighting phenomena. Examples of various methods of statistical data analysis include data visualization, regressions, correlation, inference (Roberts et al, 2019;Lemenkova, 2019d), velocity modeling using grid based travel-time calculation method (Fujie et al, 2006), regression analysis of variables (Lemenkova, 2019c), factor analysis (Tucker, 1964;Lemenkova, 2018c), clustering and data grouping (Dumont et al, 2018;Lemenkova, 2019h). As for data instruments, examples of application include R programming language (Kotov & Pälike, 2017Lemenkova, 2018a), Python programming language (Yu et al, 2019;Lemenkova, 2019b), SPSS Statistics (Lemenkova, 2019e), Gretl (Lemenkova, 2019d).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported methods, approaches and algorithm to better process and model data aimed at highlighting phenomena. Examples of various methods of statistical data analysis include data visualization, regressions, correlation, inference (Roberts et al, 2019;Lemenkova, 2019d), velocity modeling using grid based travel-time calculation method (Fujie et al, 2006), regression analysis of variables (Lemenkova, 2019c), factor analysis (Tucker, 1964;Lemenkova, 2018c), clustering and data grouping (Dumont et al, 2018;Lemenkova, 2019h). As for data instruments, examples of application include R programming language (Kotov & Pälike, 2017Lemenkova, 2018a), Python programming language (Yu et al, 2019;Lemenkova, 2019b), SPSS Statistics (Lemenkova, 2019e), Gretl (Lemenkova, 2019d).…”
Section: Discussionmentioning
confidence: 99%
“…Hiyerarşik kümeleme yöntemi her ne kadar birbirinden mutlak olarak ayrılmış kümeler yaratmaya çalışmasa da (Dumont et al 2018), HK'de elde edilen dendrogram optimal küme sayısının belirlenmesine yardımcı olabilir. Fakat dendrogramın kesme yüksekliğine karar vermek zorlu bir süreçtir (Li et al 2018, Govender andSivakumar 2020).…”
Section: çAlışma Alanıunclassified
“…(2018), kesme noktasını belirlemek için x ekseninde küme sayıları ve y ekseninde kümeler arası mesafelerin olduğu bir çizgi grafik kullanmıştır. Bu çalışmada kesme yüksekliğinin seçimi, grafikte eğiminin azalmaya başladığı nokta (dirsek formasyonu) olarak belirlenmiştir (Dumont, Reninger et al 2018).…”
Section: çAlışma Alanıunclassified
See 1 more Smart Citation
“…Airborne electromagnetics (AEM) provides information on lithology and regolith over large surfaces and/or hard-to-access areas [36][37][38][39][40]. It is able to provide plentiful pseudo-3D information about geological structures reaching a few hundred meters [41,42] and has been successfully used in many environmental studies [30,[43][44][45][46][47] particularly in volcanic settings. AEM is therefore useful to analyze the internal structure of large landslides [48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%